A fingerprint of climate change across pine forests of Sweden. (28th August 2020) - Oleksyn, Jacek; Wyka, Tomasz P.; Żytkowiak, Roma; Zadworny, Marcin; Mucha, Joanna; Dering, Monika; Ufnalski, Krzysztof; Nihlgård, Bengt; Reich, Peter B.
Abstract: Climate change has likely altered high‐latitude forests globally, but direct evidence remains rare. Here we show that throughout a ≈1000‐km transect in Scots pine ( Pinus sylvestris L.) forests in Sweden, mature trees in ≈2015 had longer needles with shorter lifetimes than did trees in ≈1915. These century‐scale shifts in needle traits were detected by sampling needles at 74 sites from 2012 to 2017 along the same transect where needle traits had been assessed at 57 sites in 1914–1915. Climate warming of ≈1 °C all along the transect in the past century has driven this temporal shift in foliage traits known to be physiologically critical to growth and carbon cycling processes. These century‐scale changes in Scandinavian Scots pine forests represent a fingerprint of climate change on a fundamental biological element, the leaf, with repercussions for productivity and sensitivity to future climate, which are likely to be mirrored by similar changes for evergreen conifers across the boreal biome. Abstract : Direct evidence of the influence of climate change on trees and forests remains scarce. By using contemporary and historical data for Scots pine, we show that from 1915 to 2015 needle longevity has been reduced and needle length has increased everywhere along a temperate–boreal transect, as predicted by fundamental relations of tree traits to the thermal environment.